Dual-immunomodulatory effects on RAW264.7 macrophages and structural elucidation of a polysaccharide isolated from fermentation broth of Paecilomyces hepiali - Baoming Tian; Renjian Liu; Qi Li; Hanshan Xu; Ming Cai; Rongfa Guan; Peilong Sun; Kai Yang (Journal of Future Foods, 2025)
More and more studies have reported the role of Paecilomyces hepiali polysaccharides in bidirectional regulation (immune enhancement and anti-inflammatory). However, there are few collaborative studies on the structure, immune enhancement, and anti-inflammatory effects of polysaccharides from the fermentation broth of P. hepiali (PHP) and the mechanisms are still unclear. The present study aimed to clarify the mechanism underlying the dual-immunomodulatory (immune enhancement and anti-inflammatory). PHP40 was precipitated with 40% ethanol from PHP40 and further purified to obtain PHP40-2. The chemical characteristics of PHP40-2 was analyzed by chemical and instrumental analyses, and the double immunomodulatory effects of RAW264.7 macrophages were investigated. PHP40-2 was a heteropolysaccharide composed of →4,6)-α-D-Glcp-(1→, →6)-α-D-Manp-(1→, α-D-Glcp-(1→, and →4)-β-D-Galp-(1→, and its molecular weight was 6.2 × 105 Da. The nitric oxide (NO) production, phagocytosis activity, and cytokine secretion were significantly increased (P < 0.05) after PHP40-2 treatment; however, PHP40-2 could inhibit NO production and cytokine secretion in LPS-induced RAW264.7 macrophages (P < 0.05). After mRNA and protein expression analysis, toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) signaling pathway was discovered to play an important role in the dual-immunomodulatory effects of PHP40-2. This study reveals that the fermentation broth of PHP is also a valuable resource and PHP40-2 has the potential to be developed as a novel functional food.